Gravity/Fluid Correspondence and Its Application on Bulk Gravity with U(1) Gauge Field - Ya-Peng Hu; Jian-Hui Zhang (Advances in High Energy Physics)
As the long wavelength limit of the AdS/CFT correspondence, the gravity/fluid correspondence has been shown to be a useful tool for extracting properties of the fluid on the boundary dual to the gravity in the bulk. In this paper, after briefly reviewing the algorithm of gravity/fluid correspondence, we discuss the results of its application on bulk gravity with a U(1) gauge field. In the presence of a U(1) gauge field, the dual fluid possesses more interesting properties such as its charge current. Furthermore, an external field Aμext could affect the charge current, and the U(1) Chern-Simons term also induces extra structures to the dual current giving anomalous transport coefficients.